2002
DOI: 10.1046/j.1468-2982.2002.00330.x
|View full text |Cite
|
Sign up to set email alerts
|

Objective Assessment of Autonomic Signs During Triggered First Division Trigeminal Neuralgia

Abstract: A total of 26 episodes of V-1 trigeminal neuralgia attacks have been recorded in two female patients. Autonomic phenomena were assessed according to a semiquantitative scale. Attacks lasted 17 +/- 5 s. Mild lacrimation without conjunctival hyperaemia, rhinorrhea or ptosis was observed, even in relatively long lasting episodes. This is in clear contradiction with SUNCT (shortlasting, unilateral, neuralgiform headache with conjunctival injection, tearing and rhinorrhea) attacks that are always dramatically accom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
43
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 17 publications
(31 reference statements)
0
43
0
1
Order By: Relevance
“…Although not statistically significant, these findings are similar to those of Cohen et al 24 The distinctions between trigeminal neuralgia, SUNA and SUNCT are certainly blurred and there is potential for overlap. However, autonomic features in classical trigeminal neuralgia are rare and have distinct characteristics, 27 which are unlikely to be included in the definition of autonomic features used for the present series. It is notable that in SUNA, in which there is greatest potential for overlap with trigeminal neuralgia, the incidence of trigger factors is lower than in SUNCT.…”
Section: Discussionmentioning
confidence: 99%
“…Although not statistically significant, these findings are similar to those of Cohen et al 24 The distinctions between trigeminal neuralgia, SUNA and SUNCT are certainly blurred and there is potential for overlap. However, autonomic features in classical trigeminal neuralgia are rare and have distinct characteristics, 27 which are unlikely to be included in the definition of autonomic features used for the present series. It is notable that in SUNA, in which there is greatest potential for overlap with trigeminal neuralgia, the incidence of trigger factors is lower than in SUNCT.…”
Section: Discussionmentioning
confidence: 99%
“…Strikingly, there was a relationship between attack duration and intensity of lacrimation, with slightly longer attacks (12-22 s) being accompanied by moderate lacrimation. The authors [11] stated that the mild-moderate degree of cranial autonomic symptoms in trigeminal neuralgia was a clear-cut difference compared to the pronounced autonomic activation reported in SUNCT. However, there are no studies that have assessed the degree of autonomic activation in SUNCT.…”
Section: Key Pointsmentioning
confidence: 95%
“…Sjaastad et al [10] reported the presence of lacrimation in 8 of 19 (42%) patients with V1 trigeminal neuralgia; conjunctival injection and rhinorrhoea were also present in some patients. Subsequently, Pareja et al [11] recorded 26 attacks from two patients with V1 trigeminal neuralgia, 81% of which were accompanied by mild lacrimation. Strikingly, there was a relationship between attack duration and intensity of lacrimation, with slightly longer attacks (12-22 s) being accompanied by moderate lacrimation.…”
Section: Key Pointsmentioning
confidence: 99%
“…First division involvement in trigeminal neuralgia is uncommon, being seen in approximately 9% of cases,5 but can occasionally be associated with mild autonomic features, such as tearing 6. SUNCT and SUNA are differentiated from first division trigeminal neuralgia by the prominence of the autonomic features (tearing, eye lid oedema, rhinorrhoea and conjunctival injection), longer duration of attacks, the absence of a refractory period to trigger factors and relative lack of response to carbamazepine 1 7–9…”
Section: Introductionmentioning
confidence: 99%